"Targets-Plans-Decision": A framework to identify the size of protected areas based on the balance of ecological protection and economic development. (15th February 2022) - Yu, Chaoyue; Gao, Yang; Wang, Chenxu; Chen, Tianqian; Wang, Jiabin; Lu, Qingling
Abstract: A framework called "Targets-Plans-Decision" (TPD) was established for identifying the size of adequate protected areas (PAs) based on the combination of species distribution probability prediction method, systematic conservation planning (SCP) theory, and protection efficiency analysis, to achieve a balance between ecological protection and economic development. The first step of the framework is to determine the protection targets. In this study, the protection targets were defined as important habitats and important ecosystems. The second step is to identify the PAs plans of different sizes. We adopted a SCP method, which takes into account cost-effectiveness while delineating the PAs. The third step is to determine the optimal size of the PAs through ecological protection efficiency analysis. We constructed the protection efficiency index (PEI), which is the protection cost per unit area. Then we used Kaya identity (a structural decomposition method) to decompose PEI. The decomposed PEI included value density (ecological value per unit area) and value cost (cost to realize unit ecological value). By analyzing the changes of the two, the optimal size of the PAs can be determined. We took Nanchang as an example to conduct an empirical study to verify the usability of the TPD framework. The result shows the TPD framework proposed in this study can effectively identify the optimal size of PAs and contribute to forming a cost-effective ecological protection plan. When the size of PAs was set to 70% of the important habitats and important ecosystems, it was most beneficial for ecological protection. Furthermore, the optimal protection efficiency plan recommended by the TPD framework improved the efficiency of ecological protection. The TPD framework can serve as a basis for the size identification of PAs and also support the delineation of PAs worldwide. Graphical abstract: Image 1 Highlights: Determining the size is a key issue in the delineation of the protected areas. A framework was established to determine the size of protected areas. We took Nanchang City as an example to conduct an empirical study. 70% was identified as the optimal size for the study area. The framework can support size identification of protected areas worldwide.